2022
DOI: 10.1111/rec.13713
|View full text |Cite
|
Sign up to set email alerts
|

Creating entrances to tree cavities attracts hollow‐dependent fauna: proof of concept

Abstract: Redressing the paucity of tree hollows is essential for conservation of hollow‐dependent fauna in many landscapes around the world. We describe a method of accelerating availability of natural hollows in regenerating landscapes by mechanically creating entrances in tree stems that have existing voids or internal decay but have not yet developed entrances. We trialed this method in woodland and forest of south‐eastern Australia in 39 stems in the closely related tree genera Eucalyptus and Angophora. Exploratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the short term, artificial nesting boxes may supplement hollow availability in some forest stands. However, they have different thermal properties (Ellis et al., 2022), can be exploited by predators of target species (Stojanovic, Owens, et al., 2021), and are not a realistic long‐term solution for hollow‐provision (Gibbons & Lindenmayer, 1996). A more promising approach for increasing hollow densities is the mechanical drilling of access holes in hollow trunks and limbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the short term, artificial nesting boxes may supplement hollow availability in some forest stands. However, they have different thermal properties (Ellis et al., 2022), can be exploited by predators of target species (Stojanovic, Owens, et al., 2021), and are not a realistic long‐term solution for hollow‐provision (Gibbons & Lindenmayer, 1996). A more promising approach for increasing hollow densities is the mechanical drilling of access holes in hollow trunks and limbs.…”
Section: Discussionmentioning
confidence: 99%
“…A more promising approach for increasing hollow densities is the mechanical drilling of access holes in hollow trunks and limbs. These constructed hollows can have similar thermal qualities to naturally occurring hollows and will likely persist for many years (Ellis et al., 2022; Griffiths et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An additional technique for constructing hollows is to use drills to mechanically create entrances in live trees with internal decay or hidden voids which have not developed entrances. A recent study showed that such hollows were rapidly used by wildlife, and temperatures inside the hollows fluctuated by 4 °C in summer whereas ambient temperatures fluctuated by 21 °C [ 52 ]. Hollows created with drills and auger bits may therefore be useful for creating artificial hollows, particularly if the aim is to create small hollows for smaller hollow-dependent animals such as microbats.…”
Section: Discussionmentioning
confidence: 99%